Epidemiologic significance of Toxoplasma gondii infections in chickens (Gallus domesticus): the past decade. Issue 12 (14th October 2020) - Dubey, J. P.; Pena, H. F. J.; Cerqueira-Cézar, C. K.; Murata, F. H. A.; Kwok, O. C. H.; Yang, Y. R.; Gennari, S. M.; Su, C.
Abstract: Toxoplasma gondii infections are common in humans and animals worldwide. Domestic free-range chickens ( Gallus domesticus ) are excellent sentinels of environmental contamination with T. gondii oocysts because they feed on the ground. Chickens can be easily infected with T. gondii ; however, clinical toxoplasmosis is rare in these hosts. Chickens are comparatively inexpensive and thus are good sentinel animals for T. gondii infections on the farms. Here, the authors reviewed prevalence, the persistence of infection, clinical disease, epidemiology and genetic diversity of T. gondii strains isolated from chickens worldwide for the past decade. Data on phenotypic and molecular characteristics of 794 viable T. gondii strains from chickens are discussed, including new data on T. gondii isolates from chickens in Brazil. This paper will be of interest to biologists, epidemiologists, veterinarians and parasitologists.